CUTTING OPTIMIZATION LUMBER ON BLANKS FOR PARQUET BOARDS (Innovation in Woodworking Industry and Engineering design, 2026)
The most common malformations ofbirch are knots, rot, and the curvature of thefalse nucleus.False heartwood not allowed in theblanks always without any restrictions. Thisarea has a low permeability of the wood, thetensile strength along the fiber toughness. Inbirch false core easily crack. False heartwoodis resistant to rot less than the sapwood.Since the size of the false nucleus depends onthe age of trees, it follows that the diameterbetween the diameter of sawlogs and heartwoodcorrelation exists. Using data from thebulkhead material was determined by thedependence of the diameter of the heartwoodof the diameter of sawlogs in the butt.The experimental results showed thatwith decreasing length of the assortment of„n“ time deflection also decreases by abouta „n“ time, that is, the value of the curvatureof the assortment, expressed in % change ofits length remains virtually unchanged. Inthis case, increase the yield of blanks canindividual approach to cutting of timber.